Determinan Motivasi, Potensi Berbasis Kompetensi Serta Pelatihan dan Pengembangan terrhadap Kinerja Karyawan yang Dimoderasi Pengalaman Kerja Balai Lelang: Studi Kasus Balai Lelang XYZ - Halimatussaadah, Halimatussaadah; Faeni, Dewi Puspaningtyas (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: To determine the effect of motivation, competency-based potential, training and development simultaneously on employee performance moderated by work experience. Research methodology: This study uses a quantitative approach, a questionnaire instrument distributed to 198 people at the XYZ auction house. Results: Motivation, Collective Motivation, Competency-Based Potential, and Training and Development have a significant effect on employee performance. Competency-Based Potential, Training and Development do not have a significant effect on employee performance. The Moderating Role of Work Experience does not moderate the relationship between motivation and performance. Limitations: This study was conducted at the XYZ auction house. The variables studied are related to motivation, competency-based potential, training and development on performance which is associated with the work experience variable as a moderating variable. Contribution: Providing practical recommendations to improve employee performance through more effective motivation, competency development, and training and development programs.